FACTORS AFFECTING THE TOTAL FOREIGN EXCHANGE RESERVE ADEQUACY OF THE CENTRAL BANK: TURKEY AND AZERBAIJAN - Gunduz Jamalzade; Arif Saldanli; Elgiz Jamalzade (Agora International Journal of Economical Sciences (AIJES), 2024)
International foreign exchange reserves are widely acknowledged as a global medium of exchange that possesses a readily available characteristic. Official public assets, which are foreign assets kept and organized by the monetary authorities of countries, serve as a complement to foreign exchange reserves. Adequate levels of foreign exchange reserves are necessary for nations to meet their payment commitments and sustain the stability of their currency. The primary rationale for the Central Bank's decision to maintain liquid foreign exchange reserves is to establish a safeguard against any speculative assaults or fluctuations in the trade balance. The primary objective of this research was to ascertain the many elements that influence the sufficiency of the aggregate foreign exchange reserves in Azerbaijan and Turkey. The article examined the sufficiency of the gross foreign exchange reserves of the Central Bank of the Republic of Azerbaijan (CBAR) and the Central Bank of the Republic of Turkey (CBRT) based on the ideal reserve ratios recommended by the IMF. Following an extensive examination of theoretical and conceptual literature, this study aims to assess the sufficiency of the Gross Foreign Exchange Reserves held by the CBAR and CBRT. The proposed optimal reserve ratios are utilized to elucidate the reserve adequacy of these countries, while considering the theoretical relationship between the variables. To achieve this objective, a logit regression analysis was conducted using the data spanning from 2012 to 2022. The results indicate that there is a positive and statistically significant relationship between interest rates and the overall adequacy of foreign exchange reserves. Considering the influence of interest rates on economic stability and financial performance, this outcome is anticipated. Furthermore, it was shown that the exchange rate variable exhibited a statistically significant negative impact on the preceding period. The present empirical study offers an overview of the various elements that influence the sufficiency of the aggregate foreign exchange reserves of Azerbaijan and Turkey. The findings of this study offer crucial insights to decision makers regarding the variables that must be considered when overseeing foreign exchange reserves.
Keywords: 330